2005
DOI: 10.1097/01.ftd.0000166041.97524.50
|View full text |Cite
|
Sign up to set email alerts
|

3,4-Methylenedioxymethamphetamine (MDMA) Intoxication in an Infant Chronically Exposed to Cocaine

Abstract: Accidental ingestion of 3,4-methylenedioxymethamphetamine (MDMA, ecstasy) was detected in an infant admitted at the Pediatric Emergency Department by drug testing in urine. Concentrations of MDMA and its principal metabolite 4-hydroxy-3-methoxymethamphetamine (HMMA) in the infant's hydrolyzed urine were 11.7 mg/L and 34.4 mg/L, respectively. Apparent febrile convulsions and cardiovascular side effects resolved within 1 day after treatment with benzodiazepines. Chronic exposure to cocaine was evidenced by segme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 14 publications
2
16
0
1
Order By: Relevance
“…A national survey in Australia conducted in 2001 revealed that 5% of teenagers and 10% of young adults had used ecstasy at least once in the preceding year [40]. Although self-reported substance use is an imperfect measure, the conclusion that ecstasy use is prevalent is generally supported by other indices of drug use including arrests [123], drug seizures [143], hair analyses [69], emergency room records [53,98,114], and coroner's reports [138].…”
mentioning
confidence: 99%
“…A national survey in Australia conducted in 2001 revealed that 5% of teenagers and 10% of young adults had used ecstasy at least once in the preceding year [40]. Although self-reported substance use is an imperfect measure, the conclusion that ecstasy use is prevalent is generally supported by other indices of drug use including arrests [123], drug seizures [143], hair analyses [69], emergency room records [53,98,114], and coroner's reports [138].…”
mentioning
confidence: 99%
“…Many of the previously published articles primarily discuss poisoning from accidental methamphetamine ingestions in children. Rhabdomyolysis, sudden death, and other known complications for stimulant toxicity were reported (16)(17)(18)(19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 97%
“…Considering this child's age, the results suggest that passive environmental exposure in young children may have highly toxic, even potential lethal, effects, probably due to their immature metabolizing capacity. In fact, previous cases of symptomatic chronic intoxication by cocaine have been described, but with lower concentration of cocaine in hair in comparison with adult hair concentrations [25-29]. …”
Section: Discussionmentioning
confidence: 99%